Diabetic ketoacidosis complicated by supraventricular tachycardia in a young adult: a case report - Ayón-Aguilar, Jorge; Valladares-Villalobos, Jesús; Santos-López, Gerardo; Méndez -Martínez, Socorro (Investigación Clínica, 2018)
Diabetic ketoacidosis (DKA) is one of the most common serious metabolic complications of diabetes in adolescents and young adults. Compli- cations are due to metabolic acidosis, electrolyte abnormalities, acute renal failure and respiratory distress. Serum electrolyte abnormalities are common in DKA. Such serum electrolyte alterations, including acidosis, have been as- sociated with the development of cardiac arrhythmias. We report the case of a 29-year-old man whose parents have diabetes mellitus. His illness began six months earlier with a weight loss of 15 kg. He did not seek for medical atten- tion. The patient presented in a family medical unit with drowsiness and dehy- dration. On examination, his blood pressure was 90/60 mmHg, pulse rate 216 beats/minute, respiratory rate 32 cycles/minute, and temperature 36.5°C. His random blood glucose was 458 mg/dL with ketonuria. His electrocardiogram showed supraventricular tachycardia. He was referred to a second level hospital where he was admitted into the Intensive Care Unit (ICU) after three hours of stabilization. The patient was discharged in good condition 11 days after his admission to the hospital and was to continue treatment with glargine insulin (1 UI/kg) at home. He was also advised on healthy nutrition, blood glucose target of 150 mg/dL and follow-up in the Outpatient Department of Cardiology and Internal Medicine.